Pengaruh Penggunaan Media Gambar Bergerak Terhadap Motivasi Belajar Bahasa Arab Siswa Kelas VIII MTs Ma’arif Pemahan Ketapang - Nurlita, Eka; Rahmap, Rahmap; Arifudin, Arifudin (Armala, 2024)
The purpose of research is to determine the motivation of learning Arabic used moving image media and the effect of used moving image media on motivation learn Arabic especially for students class VIII at MTs Ma’arif Pemahan. The type of research is an experiment with a quantitative approach and the method used is Quasi Eksperimental. Source of researcher’s data were students class VIII MTs Ma’arif Pemahan which totals 28 students. Data collection techniques are questionnaires, direct observation and documentation. Data analysis techniques used are percentage and simple linear regression test. The result of research are: (1) Learning motivation in the process of students learning Arabic using moving image media has a positive impact. Based on direct observation it can be seen that students arrive on time, listen to the lesson material presented well, complete assignments with their own efforts and enthusiastically follow the series of learning processes until the end. (2) The positive effect of using moving image media on motivation learn Arabic is 92.5%, this percentage can be seen in the output results coefficient of determination (R Square) which has a positive value of 0.925. The results of the hypothesis test sigma value of the independent variable is 0.001 < 0.05, then is accepted, it can be concluded that there is an effect of use moving image media on motivation learn Arabic for students class VIII at MTs Ma'arif Pemahan.